Impact of the Safe Childbirth Checklist on health worker childbirth practices in Luapula province of Zambia: a pre-post study - Sandra Mudhune; Sydney Chauwa Phiri; Marta R. Prescott; Elizabeth A. McCarthy; Aaron Banda; Prudence Haimbe; Francis Dien Mwansa; Angel Mwiche; Francis Bwalya; Micheck Kabamba; Hilda Shakwelele; Margaret L. Prust (BMC, 2018)
Abstract Background A strong evidence base exists regarding routine and emergency services that can effectively prevent or reduce maternal and new-born mortality. However, even when skilled providers care for women in labour, many of the recommended services are not provided, despite being available. Barriers to the provision of appropriate childbirth services may include lack of availability of supplies, limited health worker knowledge and confidence, or inadequate time. The WHO Safe Childbirth Checklist (SCC) includes reminders for evidenced-based practices at specific points in the childbirth process. Zambia is currently considering nation-wide adoption of the SCC, but there is a need for context-specific evidence. Beginning in September 2017, a program is being implemented in Nchelenge District to pilot use of the SCC, along with coaching that focuses on strengthening the systems that allow the essential practices in childbirth to be performed. Methods This study will use a pre-post study design to measure health worker adherence to the essential practices for delivery care outlined in the SCC. Data will be collected through observations of health workers as they care for mothers during childbirth at four facilities. Data collection will take place before the start of the intervention, at 3 months, and at 6 months post-intervention. The primary outcome interest is the change in the average proportion of essential childbirth practices completed. A health worker questionnaire will be administered at the time that the SCC is introduced and 6 months later to gather their perspectives on incorporating the SCC into clinical practice in Zambia. Discussion Findings are expected to inform plans for introducing the SCC in Zambia. This evaluation will aim to understand uptake and impact of the SCC and associated coaching in the context of a basic level of mentorship that the government could feasibly provide at a national scale. Trial registration Clinical Trials.gov (NCT03263182) Registered August 28, 2017.